DISCOVERY LEARNING MODEL IN INTEGRATED THEMATIC LEARNING FOR ELEMENTARY SCHOOL STUDENTS - Rahmadhani, Sary; Yunisrul, Yunisrul; Helsa, Yullys (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
Discovery learning model is a learning model that develops the students’ activities in learning by discovering and investigating their own knowledge, so that it is consistent with student-centered integrated thematic learning. The purpose of this study is to describe the Discovery Learning model in integrated thematic learning for elementary school students. This research uses comparative research by comparing some CAR existing literature studies using successful and appropriate Discovery Learning model, so it can be used in elementary school. Based on the descripton and result of the studies, it can be seen that Discovery Learning model can affect integrated yhematic learning in elementary school.